A 'smart tire' for estimating the tire force and the extents of the influences of specific factors. (November 2017) - Zhu, Xiaolong; Lu, Dang
This paper describes an intelligent device for detection of the mechanical characteristics of a tire and its test method. When deformation of the operating tire occurs, by tracking the displacements of fluorescent marker points with a camera, a neural network algorithm is applied to obtain the tire forces. The FTire model is used to fit the experimental curves obtained by measuring the mechanical properties in order to compare whether the test data agree with the actual motion law of the tire. The proposed system bypasses the use of a tire-testing machine and a six-component sensor to measure the force and the torque, and it can achieve real-time measurement and computation without isolating the tire and the vehicle. The proposed method is simple, possesses a compact structure, is easy to operate, and has low costs.